Unsettling postscripts and epilogues in A. S. Byatt’s Possession and Ian McEwan’s Atonement - Armelle Parey (Sillages Critiques)
This paper proposes to look at two contemporary British novels that, contrary to traditional practice, use their final pages to unsettle the conclusion reached earlier, and leave the reader in a state of uncertainty. Both A. S. Byatt’s Possession, a Romance (1990) and Ian McEwan’s Atonement (2001) play games with their readers when, rather than being part of a deflating and decelerating process of conclusion, the closing pages prolong and encourage rather than put an end to “retroactive reading” and “retrospective patterning”. Indeed, the last textual sections of each novel point to discrepancies or indeed constitute disjunctures themselves. In order to fully appreciate the means and effects of the dissonance established by the final textual section of these novels, this paper first looks at postscripts and epilogues as unlikely places for disruption before considering how the final dissonance affects the sense of poetic justice previously reached. Finally, the paper examines how this last-minute reversal (or confirmation) of poetic justice is linked to the powerful figure of the storyteller.